ANALISIS LINGKUNGAN LAHAN TEMPAT PEMBUANGAN SAMPAH TERPADU TERHADAP KESEHATAN MASYARAKAT SEKITAR STUDI KASUS : TEMPAT PEMBUANGAN SAMPAH TERPADU PIYUNGAN (TPST) - Muhammad Alfin Zuchriyastono; Eko Priyo Purnomo (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2020)
Frequently planning and structuring spatial governance do without having a correct understanding of human behaviors and perceptions that are sometimes unexpectedly used. The fact that use the environment is excessive and not optimal in facilitating human needs and desires, this is related to the increase in population, this effect has an impact on increasing the amount of community waste consumption, but it is not balanced with the number of existing trash bins. Dirt or rubbish in Bantul Regency is a serious problem, where is the garbage collection state located in the DIY Province focused only on the final shelter Piyungan as a final attempt at garbage disposal. Because there is a buildup in temporary landfills, this is certainly in direct contact with the health of the surrounding community, especially people who are live in Piyungan, they are directly adjacent to a landfill or rubbish dump. The purpose of this study was to find out information about relation between waste with public health issues. This research was taken by qualitative research methods, namely research in which data were obtained by means of descriptive analysis techniques. Keywords : Environmental Limitations, Garbage, and Public Health